Colombian publicists before the 1848 French Revolution, during the second half of the 19th century - Becerra Mora, José Camilo (Universidad Pedagógica y Tecnológica de Colombia, 2021)
In the mid-19th century, Nueva Granada started a new phase of its democratic experience characterized by the appearance of the Liberal and Conservative parties. Faced with this newpolitical scenario, the public writers of Nueva Granada who were linked to those parties sought to enrich their political interventions through the reading of foreign political events. It was also through this means that they sought to structure their partisan identities. This article studies different readings regarding the French Revolution of 1848 in the Colombian political scenario of the second half of the 19th-century. Through the analysis of the newspapers and other printed media, such as books, brochures and leaflets, the different notions of the French Revolution were reconstructed in Colombia during the second half of the 19th-century. The text is divided into three sections. The first section examines the attention paid to the Revolution by the Nueva Granada press during 1848. The second section reconstructs the conservative arguments about the link between the Nueva Granada Liberals and the French socialists. In the third section, Liberal interpretations of French socialist thinking are explored. This analysis has shown the richness and originality of Colombian political thinking in the 19th century, not yet widely explored in various aspects.